Impaired glyoxalase activity is associated with reduced expression of neurotrophic factors and pro-inflammatory processes in diabetic skin cells - Reichert, Olga; Fleming, Thomas; Schmelz, Martin (Experimental dermatology, 2017)
Patients suffering from type II diabetes develop several skin manifestations including cutaneous infections, diabetic dermopathy, diabetic bullae and acanthosis nigricans. Diabetic micro- and macroangiopathy as well as diabetic neuropathy are believed to play a crucial role in the development of diabetic skin disorders. A reduced cutaneous nerve fibre density was reported in diabetic subjects, which subsequently leads to impaired sensory nerve functions. Using an innervated skin model, we investigated the impact of human diabetic dermal fibroblasts and keratinocytes on porcine sensory neurons. Diabetic skin cells showed a reduced capacity to induce neurite outgrowth due to a decreased support with neurotrophic factors, such as NGF. Furthermore, diabetic keratinocytes displayed insulin resistance and increased expression of pro-inflammatory cytokines demonstrating the persistent effect of diabetes mellitus on human skin cells. Dysregulations were related to a significantly reduced glyoxalase enzyme activity in diabetic keratinocytes as experimentally reduced glyoxalase activity mimicked the increase in pro-inflammatory cytokine expression and reduction in NGF. Our results demonstrate an impaired crosstalk of diabetic skin cells and sensory neurons favouring hypo-innervation. We suggest that reduced methylglyoxal detoxification contributes to an impaired neurocutaneous interaction in diabetic skin.
First published: 16 June 2016
Gesehen am 04.05.2018